The Correlation Between Eco-Airport Implementation and Organizational Commitment to the Intention of Employee’s Green Behavior - Indah Mulyanda; Sugeng Santoso; Asep Rudiana Rachmat; Wahyudi Wahyudi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Climate change and the environment are vast topics and are becoming all parties' concerns nowadays. From 2010 to 2020, Indonesia’s average financial loss due to hydrometeorology each year was 22.8 trillion. The environmental issues that cause financial loss become not only the country’s concern but also institutes and companies in Indonesia. Eco-airport is one of Soekarno-Hatta airport’s efforts to preserve the environment. The implementation of the eco-airport also consists of employees committed to the organization. This research objective is to understand the correlation between eco-airport implementation and organizational commitment to employees’ green behavior. A method is a quantitative approach using cluster sampling and data regression analysis techniques for proofing hypothesis models with 100 samples. This research results show that eco-Aiport implementation and organizational commitment have a linear correlation, significantly influencing employees’ green behavior.